An improved ip-iq harmonic detection method - GONG Mao-fa; ZHANG Xu; ZHU Yi-kai (Gong-kuang zidonghua, 2013)
The paper introduced basic theory of ip-iq method based on instantaneous reactive power theory, and pointed out that there is error of amplitude and phase of active current component of fundamental wave detected by traditional ip-iq method because of phase difference between power grid voltage and its positive-sequence component. It proposed an improved ip-iq harmonic detection method. The improved method acquires synchronous rotation signal through combining positive-sequence voltage components with phase shift operator, which reduces detection error caused by three-phase voltage asymmetry, and introduces current mean value theory to replace low-pass filter, so as to improve dynamic response capability of harmonic detection. The Matlab simulation results showed the improved method can detect positive-sequence active current of fundamental wave correctly under condition of three-phase voltage asymmetry and has good dynamic response performance.